Improved efficiency by insertion of Zn1−xMgxO through sol-gel method in ZnO/Sb2Se3 solar cell. (June 2018) - Li, Kanghua; Kondrotas, Rokas; Chen, Chao; Lu, Shuaicheng; Wen, Xixing; Li, Dengbing; Luo, Jiajun; Zhao, Yang; Tang, Jiang
Highlights: Sol-gel process to obtain smooth and compact ZnO and Zn1−x Mgx O thin films. We sandwiched a thin Zn1−x Mgx O layer at the hetero-interface of ZnO/Sb2 Se3 . 4.45% PCE in our Sb2 Se3 solar cells employs ZnO/Zn0.9 Mg0.1 O buffer layer. Abstract: Antimony selenide (Sb2 Se3 ) is a new thin film photovoltaic material and has received great research attention these days. ZnO, a nontoxic and wide bandgap material, has been successfully applied as the buffer layer in Sb2 Se3 solar cells. Device with high efficiency and exceptional stability has been obtained, and ZnO is thus regarded as the most-promising buffer layer for Sb2 Se3 photovoltaics. Herein we reported a simple sol–gel method to deposit ZnO film and construct ZnO/Sb2 Se3 heterojunction solar cells. We applied one-step annealing process to obtain smooth and compact ZnO and ZnO/Zn1−x Mgx O thin films. We revealed that 10% Mg content was optimal for the sandwiched Zn1−x Mgx O layer and finally obtained 4.45% device performance. Through careful characterization, we found out that the insertion of Zn0.9 Mg0.1 O upshifted the Fermi-level, leading to higher built-in potential ( VBi ) and consequently larger open circuit voltage ( VOC ); it also promoted [2 2 1] orientation in Sb2 Se3 films and reduced interfacial defects of PN junction, enhancing short-circuit current density ( JSC ).